Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. V. coffe-desks. (H.S. Stuttman Co, 1975)
623-776 p.; 25 cm.